2015
DOI: 10.1186/s12884-015-0549-5
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of financial incentives for breastfeeding: thematic analysis of readers’ comments to UK online news reports

Abstract: BackgroundWhilst it is recommended that babies are breastfed exclusively for the first six months, many mothers do not maintain breastfeeding for this length of time. Previous research confirms that women and midwives value financial incentives for breastfeeding, but limited research has explored the wider acceptability of these interventions to the general public. This paper examines opinion towards financial incentives for breastfeeding using reader responses to UK on-line media coverage of a study undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 64 publications
3
47
2
1
Order By: Relevance
“…[94][95][96][97] However, this was not a strong finding in the current work. The systematic review was not able to draw generalisable conclusions concerning effectiveness, but did find some instances in which financial incentives were effective at encouraging uptake.…”
Section: Potential Effectivenesscontrasting
confidence: 75%
See 1 more Smart Citation
“…[94][95][96][97] However, this was not a strong finding in the current work. The systematic review was not able to draw generalisable conclusions concerning effectiveness, but did find some instances in which financial incentives were effective at encouraging uptake.…”
Section: Potential Effectivenesscontrasting
confidence: 75%
“…This appears to be a common phenomenon in qualitative work on the acceptability of health-promoting financial incentives. 96,97 It is not clear exactly what this reflects: perhaps that participants dislike the idea of incentives so much that they would rather not talk about them, or perhaps that they dislike them but find it hard to articulate specifically why, choosing instead to move the conversation to easier ground. Furthermore, many of the alternative approaches to maximising vaccination uptake proposed by participants reflect existing guidance and good practice 11 and known attitudes of parents to vaccination.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…34,38,55 In terms of sources of frames, our media analysis reconfirmed previous results showing that journalists often don't mention their source of information when reporting on health issues. 56 In alignment with previous media analyses, 41,57 the results of this study show that the quantity of media coverage appears to be linked to specific events.…”
Section: Discussionsupporting
confidence: 76%
“…61 Giles and associates' study of public opinions toward financial incentives for breastfeeding found that the public often argued against the policy because they were concerned that the government was interfering with everyday life and the policy reinforced a feeling of failure or guilt in mothers unable to breastfeed. 55 Arguments opposing tobacco policies often frame the issue as restrictions on freedom of choice as well as unnecessary government interference. 34,38 Studies of public health policy have found that Americans often value and adamantly defend the freedom of choice, even unhealthy choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation